Ultrasound biomicroscopic analysis of pseudophakic pupillary block glaucoma induced by Soemmering's ring. Issue 10 (1st October 2000) - Kobayashi, Hiroshi; Hirose, Mio; Kobayashi, Kaori
Abstract : AIM: To perform ultrasound biomicroscopic analysis of pseudophakic pupillary block glaucoma induced by lens capsule and a Soemmering's ring and its resolution, and to elucidate the pathophysiology of this glaucoma. METHODS: A woman with pseudophakic pupillary block glaucoma underwent successful neodymium:YAG (Nd:YAG) laser photodisruption of the lens capsule through a laser iridotomised coloboma with resolution of the pupillary block. The Humphrey ultrasonic biomicroscope model 840 was employed to observe the anterior segment before and after laser photodisruption. RESULTS: Ultrasound biomicroscopic examination revealed the intraocular lens (IOL) was displaced forward, shallowing the central anterior chamber. The anterior hyaloid face was relatively posterior to the posterior capsule. The iris was in apposition to the anterior capsule, which was in touch with the IOL optics. A massive Soemmering's ring, which extended from the IOL optics to the ciliary processes, was displaced anteriorly. The Soemmering's ring consisted of several tightly packed layers. The ciliary processes rotated anteriorly. After Nd:YAG laser photodisruption of the capsule, ultrasound biomicroscopic images showed the resolution of the pupillary block and the anterior rotation of the ciliary process. The Soemmering's ring moved posteriorly, and the layers in the ring became loose. CONCLUSIONS: A massive Soemmering's ring may one of potential causes of pupillary block after cataract surgery. Ultrasound biomicroscopy is potentially useful as a non-invasive diagnostic technique for clinical diagnosis and differentiation between Soemmering's ring induced pupillary block glaucoma and other forms of pupillary block.